Pengembangan Media Papan Jurang (Penjumlahan dan Pengurangan) dalam Meningkatkan Kemampuan Berhitung Siswa Kelas I di SDN 2 Kalijaga - Zahrotul Hayati; Ahmad Sulhan; Djuita Hidayati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is motivated by the lack of numeracy skills in grade 1 students and the lack of use of learning media that can help students in learning mathematics, and in this study the researcher used the gap board media (addition and subtraction) in improving students' numeracy skills. Therefore, this study aims to determine the feasibility, practicality and effectiveness of the gap board media (addition and subtraction) in improving the numeracy skills of grade 1 elementary school students. This study used a Research and Development (R&D) method with the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study subjects consisted of media expert validators, material experts, and 23 first-grade students (10 girls and 13 boys). Data were collected through questionnaires, tests, interviews, and observations, then analyzed using qualitative and quantitative techniques. The results showed that the "ravine board" media received a feasibility rating of 98.6% from the media experts and 95.4% from the material experts, categorizing it as very feasible. The practicality rating was 100% from teachers and 97% from students, categorizing it as very practical. The effectiveness test results showed a significance value of 0.268, indicating a normally distributed data. A paired t-test indicated a significant difference between the pretest and posttest scores with a p-value <0.05. Furthermore, the N-Gain test result of 0.82 is considered high. Thus, the ravine board is deemed feasible, practical, and effective for use in teaching arithmetic to first-grade elementary school students.